The Influence of Effective Time: Berthing Time on Berth Occupancy Ratio at Mirah Port, Tanjung Perak. - Wiratama, Ahmad Alfan; Sianturi, Intan; Agustina, Eka Nurmala Sari; Rahayu, Trisnowati (Management Department, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
Objective – This research aims to analyze the impact of Effective Time : Berthing Time on the Berth Occupancy Ratio at Mirah Port, Tanjung Perak, by assessing its efficiency and compliance with operational standards.Design/methodology/approach – The research applies a quantitative method with simple linear regression analysis. The data were obtained from monthly Performance Standards Reports of KSOP Utama Tanjung Perak from 2020 to 2024. The analysis was conducted using SPSS version 26 to determine the statistical significance of Effective Time : Berthing Time’s impact on Berth OccupancyRatio.Findings – The analysis shows that the Effective Time to Berthing Time ratio for both 2023 and 2024 consistently falls below the required minimum standard. Despite this, the Berth Occupancy Ratio remains within a safe range and does not surpass the established threshold. Further hypothesis testing demonstrates that there is a significant relationship between the Effective Time to Berthing Time ratio and the Berth Occupancy Ratio. However, this ratio only explains a small portion of the variation in BerthOccupancy Ratio, suggesting that most of the changes are influenced by other factors not covered in this study.Research limitations/implications – The research is limited to Terminal Mirah and covers only the period from 2020 to 2024. Future research should consider expanding the dataset and including other performance factors.Practical implications – Terminal Mirah should enhance operational effectiveness through infrastructure optimization, workforce training, and improved cargo handling efficiency to raise Effective Time : Berthing Time values, ensuring optimal Berth Occupancy Ratio utilization.Originality/value – This research contributes to port management studies by establishing the relationship between Effective Time : Berthing Time and Berth Occupancy Ratio, highlighting the need for improved operational efficiency to meet regulatory standards.